The effect of thermal radiation, velocity slip and viscous dissipation on MHD stagnation-point flow and heat transfer over a shrinking sheet in nanofluids with stability analysis - Ismail, N. S.; M. Isa, S. S. P.; Arifin, N. M.; Nazar, R.; Bachok, N. (University of Latvia, 2021)
Research on heat transfer problems is important in view of applications in industries and engineering. As a result, the present study examines numerically the steady MHD stagnation point flow and heat transfer over a shrinking sheet in the presence of suction, thermal radiation, viscous dissipation and velocity slip. The flow for this problem is considered in nanofluids and a Buongiorno's model is used. The boundary layer equation is derived by reducing the governing equations to an ordinary differential equation. An appropriate similarity transformation is used to convert from PDEs to ODEs. The numerical results were then processed using the bvp4c package in Matlab. The impacts of the characteristics studied were graphically represented and extensively described in this study. Dual solutions occur within a particular range of α, according to the numerical results. Finally, a stability analysis proves that there are two solutions to the problem and only one of them is stable. Tables 4, Figs 8, Refs 33.